Hear it straight from the horse's mouth: recognizing policy-induced opportunities. Issue 5 (26th May 2020) - Dai, Weiqi; Arndt, Felix; Liao, Mingqing
ABSTRACT: What types of entrepreneurs are more likely to 'stay tuned' to government policies and does it pay? Integrating work on opportunity recognition and the institution-based view, this study examines the link between the pursuit of policy-induced opportunities and firm performance. Based on data analysis of 3284 Chinese privately owned firms in 31 regions/provinces in China, we find that entrepreneurs who have past working experience within the government are more likely to stay alert to government policies involving entrepreneurial opportunities, which leads to entrepreneurial activities and ultimately firm performance. This study enriches our understanding of opportunity recognition and development by expanding it to political markets. We assess the role of institutional variation as an important factor in emerging economies. We unravel the pivotal role of entrepreneurial alertness to government policies on enhancing firm performance by strengthening entrepreneurial activities.